ANALISIS FRAUD PENTAGON TERHADAP KECURANGAN LAPORAN KEUANGAN PADA SEKTOR PERUSAHAN MANUFAKTUR YANG TERDAFTAR Di BURSA EFEK INDONESIA - Delviana Dama Yanti (Jurnal Ilmiah Manajemen Ubhara, 2021)
ABSTRACT The purpose of this research is see the effect of pentagon fraud proxied by financial targets, nature of the industry, quality of external auditors, change of auditors, number of CEOs who frequently detect fraud in financial statements. Financial statement fraud in this study was measured using the proxies of Return on Assets, Receivables, selection of audit services at public accounting firms, changes in public accounting firms, changes in directors, and the number of CEO photos. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange (BEI) in 2017-2019. This study uses a purposive sampling technique so, there are 48 financial reports from 25 manufacturing companies. The analytical method used is multiple linear regression analysis with SPSS version 20. The results of this study indicate that financial targets, nature of industry, quality of external auditors and the number of CEOs who often do not have a significant effect in the handling of fraudulent financial statements. Meanwhile, changes in auditors and changes in direction have a significant effect on fraudulent financial statements